Aligned PLLA nanofibrous scaffolds coated with graphene oxide for promoting neural cell growth. (June 2016) - Zhang, Kuihua; Zheng, Honghao; Liang, Su; Gao, Changyou
Graphical abstract: Abstract: The graphene oxide (GO) has attracted tremendous attention in biomedical fields. In order to combine the unique physicochemical properties of GO nanosheets with topological structure of aligned nanofibrous scaffolds for nerve regeneration, the GO nanosheets were coated onto aligned and aminolyzed poly-l -lactide (PLLA) nanofibrous scaffolds. Scanning electronic microscopy (SEM) and atomic force microscopy (AFM) revealed that the surface of aligned PLLA nanofibers after being coated with GO became rougher than those of the aligned PLLA and aminolyzed PLLA nanofibrous scaffolds. The GO nanosheets did not destroy the alignment of nanofibers. The characterizations of X-ray photoelectron spectroscopy (XPS) and water contact angle displayed that the aligned PLLA nanofibrous scaffolds were introduced with hydrophilic groups such as NH2, COOH, and OH after aminolysis and GO nanosheets coating, showing better hydrophilicity. The GO-coated and aligned PLLA nanofibrous scaffolds significantly promoted Schwann cells (SCs) proliferation with directed cytoskeleton along the nanofibers compared with the aligned PLLA and aminolyzed PLLA nanofibrous scaffolds. These scaffolds also greatly improved the proliferation of rat pheochromocytoma 12 (PC12) cells, and significantly promoted their differentiation and neurite growth along the nanofibrous alignment in the presence of nerve growth factor (NGF). This type of scaffolds with nanofibrous surface topography and GO nanosheets is expected to show better performance in nerve regeneration. Statement of Significance: Recovery of damaged nerve functions remains a principal clinical challenge in spite of surgical intervention and entubulation. The use of aligned fibrous scaffolds provides suitable microenvironment for nerve cell attachment, proliferation and migration, enhancing the regeneration outcome of nerve tissue. Surface modification is generally required for the synthetic polymeric fibers by laminin, fibronectin and YIGSR peptides to stimulate specific cell functions and neurite outgrowth. Yet these proteins or peptides present the poor processibility, limited availability, and high cost, influencing their application in clinic. In this work, we combined GO nanosheets and topological structure of aligned nanofibrous scaffolds to direct cell migration, proliferation, and differentiation, and to induce neurite outgrowth for nerve regeneration. The GO coating improved several biomedical properties of the aligned PLLA nanofibrous scaffolds including surface roughness, hydrophilicity and promotion of cells/material interactions, which significantly promoted SCs growth and regulated cell orientation, and induced PC12 cells differentiation and neurite growth. The design of this type of structure is of both scientific and technical importance, and possesses broad interest in the fields of biomaterials, tissue engineering and regenerative medicine.